2012
DOI: 10.1165/rcmb.2011-0074oc
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hyperoxia-Induced Lung Injury in Nitric Oxide Synthase 2 Null Mice Is Mediated via Angiopoietin 2

Abstract: Supplemental oxygen is frequently prescribed. However, prolonged exposure to high concentrations of oxygen causes hyperoxic acute lung injury (HALI), which manifests as acute respiratory distress syndrome in adults and leads to bronchopulmonary dysplasia in newborns (NBs). Nitric oxide (NO), NO synthases (NOSs), and angiopoietin (Ang) 2 have been implicated in the pathogenesis of HALI. However, the mechanisms of the contributions of NOS/NO and the relationship(s) between NOS/NO and Ang2 have not been addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 64 publications
3
32
0
Order By: Relevance
“…The net effect of the Ang2/Ang1 expression ratio is increased Ang2, which we speculate could be contributing to enhanced HALI and increased mortality in the MIFKO mice. Since increased Ang2 has been shown in mouse models and human subjects (including premature NB with RDS) to be associated with increased mortality and/or adverse pulmonary outcomes [25], [34], [35], we speculate that a decreased concentration of Ang2 could be playing a role in the protective response of the MIFTG mice in hyperoxia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The net effect of the Ang2/Ang1 expression ratio is increased Ang2, which we speculate could be contributing to enhanced HALI and increased mortality in the MIFKO mice. Since increased Ang2 has been shown in mouse models and human subjects (including premature NB with RDS) to be associated with increased mortality and/or adverse pulmonary outcomes [25], [34], [35], we speculate that a decreased concentration of Ang2 could be playing a role in the protective response of the MIFTG mice in hyperoxia.…”
Section: Discussionmentioning
confidence: 90%
“…For example, in the context of HALI, Ang2 increases vascular permeability, while Ang1 tends to stabilize the blood vessels and decreases vascular permeability. Our previously published data [25], [34] suggest that higher levels of Ang2 in response to hyperoxia exposure in the lung are detrimental in the context of HALI. Such effects in HALI would be further compounded by decreased Ang1.…”
Section: Discussionmentioning
confidence: 91%
“…A minimum of 200 cells were counted for the differential cell count (36). Total protein was measured using a DC Protein Assay (Bio-Rad) per the manufacturer's recommendations, as previously described (37).…”
Section: Methodsmentioning
confidence: 99%
“…They found that tumor necrosis factor-a-induced upregulation of inflammatory adhesion molecules by endothelial cells required Angpt-2 expression by those cells (Fiedler et al, 2006). Shortly thereafter, Bhandari et al (2012) reported that hyperoxia-induced acute lung injury in mice was ameliorated by genetic or small interfering RNA depletion of Angpt-2, and showed that bronchoalevolar lavage fluid from individuals with acute lung injury contained high levels of Angpt-2. Of note, the authors argued for an injurious role of Angpt-2 in the alveolar epithelial necrosis characteristic of this model.…”
Section: The Angiopoietin/tie2 Systemmentioning
confidence: 99%